PENDIDIKAN NON FORMAL BERBASIS MASYARAKAT DESA : (Studi pada Yayasan Pelita Hati Kabupaten Sumenep) - Hayat, Ainul (Jurnal Administrasi Publik, 2024)
Non-Formal Education Based on Village Community- (Study at the Pelita Hati Foundation, Sumenep Regency). Non-formal education can contribute to efforts to expand new job opportunities in rural areas. The design and implementation of non-formal education programs is carried out by mapping activities according to the needs of rural communities. Non-formal education carried out by the Pelita Hati Foundation, Sumenep Regency for village communities is the involvement and empowerment of local communities to assist in the process of managing cattle farms and making corn silage, through cooperation and collaboration with the Sumenep Regency government, KODIM, the private sector, and the farming community itself. By empowering the surrounding community in this activity, benefits be obtained by the community, local government, private sector and the foundation itself. The profits obtained by the Pelita Hati Foundation are used to drive the wheels of free formal education (0 rupiah) and the development of community infrastructure around the foundation's offices.